Toward psychiatry as a ‘human’ science of mind. The case of depressive disorders in DSM-5 - Castiglioni, Marco; Laudisa, Federico (Frontiers in Psychology, 2015)
The aim of this paper is to argue that a strictly reductionist approach to psychiatry represents a theoretical and clinical obstacle to a fruitful synthesis between neurobiological and sociocultural aspects of the sciences of mind. We examine the theoretical and practical motivations underlying this approach, by analyzing the case of depressive disorders, as defined in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM), and the related removal of the “bereavement exclusion clause”. We first explore the claim that DSM is atheoretical, observing that, far from being atheoretical, DSM adopts an implicit, biologically-inspired view of the mind; we show that such a view leads to a sort of circularity in the definition of depressive disorders, in which psychopharmacology seems to play a key role. We then turn to further problems deriving from this a position, analyzing the issue of placebo effects in the treatment of depressive disorders and the philosophical question of normative preconditions for psychopathological diagnosis. Finally, we address the issue of subjectivity, which, together with the related aspect of the subject’s relational context, appears to be crucial to any scientific theorizing about mental disorders, despite DSM’s attempt to exclude it. Our defence of a non-reductionist view of mental disorders, however, does not imply that we endorse any sort of metaphysical dualism, or anti-diagnostic or anti-psychiatric positions. On the contrary, we argue that adoption of a reductionist position actually undermines theoretical and clinical accuracy in explaining depressive disorders.